Influence of bottled salad dressings on the development of enamel erosion in the presence or absence of salivary pellicle - An in vitro study - Aishwarya Lakshmi Billa; Jagadeeswara Rao Sukhabogi; Dolar Doshi; Prashant Sharma; T.V.S. Subrahmanyam; Sasikala Jummala (Elsevier, 2024)
Background: Acidic beverages are believed to elevate the risk of enamel surface erosion. In addition to the intake of soft drinks, the increased consumption of salad dressings has been linked to a higher prevalence of dental erosion. Therefore, the current study aimed to investigate the influence of bottled salad dressings on the development of enamel erosion in the presence or absence of pellicle through in vitro experiment. Methods: Preliminary pH and calcium analyses of solutions were performed. Highest pH and calcium content was found for sandwich spread i.e., 4.69 and 55.4 mg/100 g grams, respectively. Eighty tooth specimens (measuring 4 × 4 × 3 mm) were prepared from extracted human premolars and randomly assigned to four groups (group 1: orange juice; group 2: eggless plain mayonnaise; group 3: sandwich spread; and group 4: thousand island dressing) with 20 samples in each group. Ten tooth specimens from each group were immersed in 20 ml of the respective solutions for 5 min (control group). The remaining ten tooth specimens from each group were submerged in 5 mL saliva vials for 3 min to facilitate salivary pellicle formation before being immersed in their respective solutions for 5 min (saliva-covered group). Pre and post-experimental assessments of enamel roughness and hardness were conducted using a surface roughness tester and Knoop Hardness indenter, respectively. Results: Overall, enamel roughness was notably elevated in the control group, with the eggless plain mayonnaise (0.52 ± 0.38) and thousand island dressing groups (0.57 ± 0.29) showing a significant increase in surface roughness post-test (p = 0.05). Nevertheless, there was no significant difference in the enamel roughness between the groups. On the other hand, regardless of the presence/absence of the salivary pellicle, a marked decrease in enamel hardness was observed among all groups except for group 3 (sandwich spread) with a mean score of 311.5 ± 82.6 (p < 0.05). Conclusion: A significant increase in surface roughness and reduction in enamel hardness was observed with salad dressings. However, in vitro formed salivary pellicle showed a protective effect against tooth erosion.